Benin Publics' Perception of Media Framing of Gender Equality for National Development in Nigeria - Nwaoboli, Emeke Precious; Aríjeníwà, Adédèjì Fred (Journal of Communication and Public Relations, 2025)
This study examines the Benin public's perceptions of media framing gender equality in Nigeria and its impact on national development. The study's rationale was to ascertain how media framing practices shape public attitudes and influence policy responses, ultimately affecting the overall advancement of gender equality in Nigeria. Anchored on framing theory, the study employed the survey research design and collected data using a structured questionnaire from 384 respondents in Benin City using the multistage sampling technique. The data were presented in tables and analyzed using frequency counts, straightforward percentages, and mean scores. Findings revealed that the media create awareness of gender equality among the Benin public to a great extent, with social media identified as the most effective platform. Also, the standard frames employed by the media on gender equality issues are social justice and political empowerment frames. However, despite recognizing the media’s effectiveness, concerns about bias and fairness persist. The researchers conclude that while media plays a significant role in raising awareness, there is considerable skepticism regarding the accuracy and bias of these portrayals. Recommendations include efforts that should be made to increase the frequency and consistency of gender equality content across all media platforms, including traditional and digital media, among others.